2010
DOI: 10.1177/0300985810363485
|View full text |Cite
|
Sign up to set email alerts
|

Tubulin Tyrosine Ligase–Like 1 Deficiency Results in Chronic Rhinosinusitis and Abnormal Development of Spermatid Flagella in Mice

Abstract: Tubulin tyrosine ligase-like 1 (TTLL1) protein is a member of the tubulin tyrosine ligase superfamily of proteins that are involved in the posttranslational polyglutamylation of tubulin in axonemal microtubules within cilia and flagella. To investigate the physiological role of TTLL1, the authors generated mice with a gene trap mutation in the Ttll1 gene that provide confirmation in a mammalian model that polyglutamylation plays an important role in some ciliary and flagellar functions. For the first time, mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 67 publications
0
73
0
Order By: Relevance
“…A morpholino-mediated depletion of the TTLL6 E-ligase in zebrafish is associated with shortening and loss of olfactory cilia (Pathak et al, 2007). In mice, mutations in either the TTLL1 E-ligase or associated protein PGs1 cause various defects in the sperm axoneme that are associated with male infertility (Campbell et al, 2002;Ikegami et al, 2010;Regnard et al, 2003;Vogel et al, 2010). Curiously, the Ttll1-deficient mice assemble structurally normal cilia in the trachea, despite low levels of tubulin glutamylation (but the motility of these cilia is strongly affected; see below) Vogel et al, 2010).…”
Section: Tubulin Ptms Regulate the Assembly Of Microtubular Organellesmentioning
confidence: 99%
See 1 more Smart Citation
“…A morpholino-mediated depletion of the TTLL6 E-ligase in zebrafish is associated with shortening and loss of olfactory cilia (Pathak et al, 2007). In mice, mutations in either the TTLL1 E-ligase or associated protein PGs1 cause various defects in the sperm axoneme that are associated with male infertility (Campbell et al, 2002;Ikegami et al, 2010;Regnard et al, 2003;Vogel et al, 2010). Curiously, the Ttll1-deficient mice assemble structurally normal cilia in the trachea, despite low levels of tubulin glutamylation (but the motility of these cilia is strongly affected; see below) Vogel et al, 2010).…”
Section: Tubulin Ptms Regulate the Assembly Of Microtubular Organellesmentioning
confidence: 99%
“…In mice, mutations in either the TTLL1 E-ligase or associated protein PGs1 cause various defects in the sperm axoneme that are associated with male infertility (Campbell et al, 2002;Ikegami et al, 2010;Regnard et al, 2003;Vogel et al, 2010). Curiously, the Ttll1-deficient mice assemble structurally normal cilia in the trachea, despite low levels of tubulin glutamylation (but the motility of these cilia is strongly affected; see below) Vogel et al, 2010). As discussed earlier for cytoplasmic microtubules, during axoneme assembly tubulin glutamylation can also act by regulating the microtubule-severing factors, specifically katanin.…”
Section: Tubulin Ptms Regulate the Assembly Of Microtubular Organellesmentioning
confidence: 99%
“…The Dnahc1 (MIM# 603332) null results in reduced tracheal cilia and sperm tail motility; however, no analysis of upper respiratory tract pathology was performed making it unclear how well this models PCD. A preliminary analysis of Ttll1 (MIM# 608955) mutants [Vogel et al, 2010] demonstrates PCD-like upper respiratory pathology, but ciliary motility and morphology has yet to be studied. These data led Ostrowski and colleagues to engineer postnatal deletion of Dnaic1 (MIM# 604366); deletion at 8-12 weeks of age avoids hydrocephalus.…”
Section: Introductionmentioning
confidence: 99%
“…All these data suggest that NME7 is involved in the biogenesis and function of motile cilia. Vogel and colleagues also reported that Nme5 -/-mice display a pathological phenotype highly suggestive of primary ciliary dyskinesia [107].…”
Section: Nm23-x4 Function In Xenopus Retinal Developmentmentioning
confidence: 96%
“…Constitutive Nme5 and Nme7 knockout mice were generated and described by Vogel and co-workers [96,107,108]. Nme7 knockout mice present defects like situs inversus (a congenital condition characterized by left-right transposition of thoracic and visceral organs and associated vasculature) and hydrocephalus [108] (Fig.…”
Section: Nm23-x4 Function In Xenopus Retinal Developmentmentioning
confidence: 99%